Cultivars and rootstocks on plants vigor of European pear Cultivares e portaenxertos sobre o vigor de plantas de pereira Europeias - Machado B.D.* (2013)
The pear (Pyrus communis) culture offers a great expansive market opportunity in southern Brazil, according to climatic conditions and soil. However, there are still some barriers that prevent satisfactory economic production, such as lack of knowledge about the best combinations of cultivars and rootstocks. The objective of the study was to evaluate the infl uence of European pear cultivars and quince (Cydonia oblonga) rootstocks on the plants vigor variables. The experiments were carried out in commercials orchards in Fraiburgo Municipality, Santa Catarina state, during the crop season of 2008/09, 09/10 and 10/11. The cultivars evaluated were 'Packham's Triumph', 'Santa Maria', 'Rocha' and 'Abbè Fetel' and the quince rootstocks EMC and Adams. The cultivars and rootstocks combinations were conducted in a spacing of 0.3mx4m between plants and rows, respectively. The vigor variables evaluated were, a. plants height increment (m); b. canopy volume increment (m3); c. truck diameter increment of the cultivars canopy (mm); d. truck diameter increment of rootstocks (mm); e. difference between the trunk diameter of cultivars canopy and rootstock (mm); f. fertility index (buds cm-1); g. total cumulative average of fresh weight of pruned branches (kg); and h. cumulative difference between the fresh and dry weight of pruned branches (kg). All combinations evaluated affected the vegetative parameters of the European pear cultivars. The combinations Abbè Fetel and Rocha grafted on Adams quince rootstocks are significant more vigorous according to increment of cultivars canopy truck diameter, plant height increment, cultivars canopy volume increment and cumulative average weight of pruned branches, when compared with others combinations. The combination Santa Maria grafted on Adams quince rootstock showed signifi cant intermediate vigor according to cultivar canopy volume increment, truck diameter of cultivar canopy and, truck diameter of rootstock. This combination presented a better proportion amongst the vigor variables and can be indicated for commercial production according to the experimental edafoclimatic conditions of southern Brazil.